SOME SHORT HISTORICAL NOTES ON DEVELOPMENT OF MATHEMATICAL LOGIC IN SOFIA - Skordev, Dimiter (Ann. Sofia Univ. Fac. Math. and Inf., 2004)
We present some information about the pre-history and the history of development of mathematical logic in Sofia. The history of the so-called Sector of Mathematical Logic (existing from 1972 to 1989) is considered in some detail.